Professional development of physics faculty and undergraduate students - Huynh, Tra (Kansas State University, 2020)
This research presents the investigation of physics students' and physics faculty members' professional development and a design methodology via which we could best support them in their professional development. In particular, the first part of this dissertation will focus on undergraduate upper-division physics students' conceptual learning and equity within lab groups. The second part of this dissertation will describe a fundamental study of faculty professional development focusing on their own experiences over time. In the last part of this dissertation, I present a study of one design methodology that can help produce more student-centered and faculty-centered professional development programs. In the first project of part I, I explore how upper-division physics students make sense and use mathematics in their physics problem-solving process. The literature has shown that students' struggles with mathematics are not simply because they lack mathematical competence. Rather, fluent and productive use of mathematics requires one to understand the physical meanings embodied in mathematical symbols, operators, syntax, etc., which can be a difficult task. For instance, in algebraic symbolization, the negative and positive signs carry multiple meanings depending on contexts. In the context of electromagnetism, I use conceptual blending theory to demonstrate that different physical meanings, such as directionality and location, could be associated with the positive and negative signs. With these blends, I analyze the struggles of upper-division students as they work with an introductory level problem where the students must employ multiple signs with different meanings in one mathematical expression. I attribute their struggles to the complexity of choosing blends with an appropriate meaning for each sign, which gives us insight into students' algebraic thinking and reasoning. The second project in part I investigates another aspect of student learning, focusing on the dynamics of lab groups that support or inhibit individual learning. In this work, I use the inchargeness framework, where inchargeness is associated with one's authority in driving the activity. I study how inchargeness changes within a collaborative group when its members have differing expertise. I present a case study of a group of three students working in an upper-division undergraduate physics laboratory. One of them has less on-task expertise than her peers due to missing a day, which reduces her relative inchargeness across two storylines: "catching up" and "moving forward". Part II of this dissertation investigates how faculty engage in long-term professional development activities, continually learning and applying various innovations into their teaching practices. I take an asset-based and agentic perspective to explore faculty experiences with on-going processes of change. We conducted longitudinal interviews with physics and astronomy faculty members from diverse backgrounds and carried out an ethnographic study regarding their long-term professional trajectories. Disciplinary professional development programs and on-going relationship with disciplinary colleagues are significant for faculty in making, appreciating, and sustaining changes. Additionally, faculty often pay attention to contextual constraints for structuring and creating changes. This analysis contributes another view to the current literature, which often focuses on how these constraints inhibit faculty processes of change. Part III of this dissertation moves from fundamental studies of professional development of students and faculty to an exploration of a methodology for effective design: personas. Personas are life-like characters that are driven by potential or real users' personal goals and needs when interacting with a product. We argue that personas can support user-centered design in educational contexts. However, the use of personas in educational research and design requires certain adjustment from its original use in human-computer interface. In this study, I propose a process of creating personas from phenomenographic studies, which helps create data-grounded personas effectively. I illustrate this process with two examples: the design of a professional development website and an undergraduate research program design. Using these examples, I hope to provide education designers and researchers a clear method of creating personas that is relatable and applicable to their own design problems.
Keywords: Upper division physics student; Conceptual blending; Methodology of personas; Inchargeness in lab groupwork; Faculty professional development; Faculty's on-going change